The Science–Policy Interface for Climate Change Adaptation: the Contribution of Communities of Practice Theory. (30th October 2013) - Iyalomhe, Felix; Jensen, Anne; Critto, Andrea; Marcomini, Antonio
ABSTRACT Climate change adaptation demands a successful science–policy interface that can enhance the translation of climate scenarios to adaptation policies. However, experience shows it is difficult to implement this interface in practice, particularly at the regional/local scale. This paper considers the communities of practice theory in a new way, by examining two model cases to highlight areas of potential opportunities and contentions with the theory, and to understand how a successful science–policy interface in climate change adaptation projects could be envisioned as a community of practice. The assumption is that the social contexts in which these projects often exist could be established by the concepts of 'communities of practice', which defines activities in a social and historical context that gives structure to the engagement of participants. We compiled cases from open‐ended survey and interactive research experience and observation, and inductively reflected on these vis‐à‐vis communities of practice. The model cases revealed challenges as well as potential opportunities for communities of practice, in that they exist within a middle space (social context) that could facilitate personal and professional relationship, promote formal and informal interactions, and are needed to negotiate different expertise and narrow apparent boundaries. We conclude that vigorous and dynamic communities of practice promise to nurture the social context in which participants in adaptation projects are potentially engaged, and thus provide a provisional support to the science–policy interface. Copyright © 2013 John Wiley & Sons, Ltd and ERP Environment.